Strategic Challenges and Integrated Models for Dual Curriculum Implementation: A Systematic Review (2015–2025) - Bening Kirana Jingga; Heru Santosa; Sugiarto Sugiarto; Kamaludin Kamaludin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
The increasing demand for globally competitive yet locally grounded education has encouraged many countries, including Indonesia, to implement dual-curriculum systems integrating national and international frameworks. In Indonesian K–12 schools, this integration commonly involves the national curriculum alongside international programs such as Cambridge, the International Baccalaureate (IB), and the International Primary Curriculum (IPC). While this model offers opportunities to enhance global competence and academic quality, its implementation remains complex and multidimensional. Schools must navigate policy alignment, teacher readiness, curriculum integration, assessment compatibility, and stakeholder coordination simultaneously. Despite growing scholarly attention, existing studies on dual-curriculum implementation remain fragmented, often focusing on isolated variables and failing to provide a comprehensive systemic synthesis. Addressing this gap, the present study employs a PRISMA-guided Systematic Literature Review of 20 peer-reviewed articles published between 2015 and 2025. Through thematic and bibliometric analyses, the study identifies dominant implementation challenges and evolving research trends. As its primary contribution, the research proposes the Integrated Dual Curriculum Implementation (IDCI) Model, a theory-grounded framework designed to support sustainable dual-curriculum practice and inform policy, leadership, and instructional strategies in Indonesia’s evolving education system.